Routine Activities, Minority Stress, and Social Support: Victimization Risk and the Lived Experiences of Transgender and Gender Non-Conforming People - Felix-Highsmith, Shanna (2021)
Even though they represent less than 1% of the general population, transgender and gender non-conforming (TGNC) people experience disproportionately high rates of nearly every type of victimization. Despite this, the theoretical literature that seeks to explain these victimization patterns is limited. In this dissertation, interviews with 52 TGNC people were conducted and analyzed using a grounded theory approach. The goal of this dissertation is to better understand the process by which TGNC people may be exposed to victimization risk. The findings from this dissertation demonstrate the possibility of using both Minority Stress Theory and the Routine Activities/Lifestyle Exposure theory in understanding TGNC peoples’ victimization experiences. The findings from this dissertation also outline processes by which TGNC peoples’ formal and informal social support networks may ultimately contribute to both minority stress and victimization risk, even though existing literature proposes that these support networks should ameliorate minority stress. Implications for future research, prevention, and intervention are also discussed